Bioeconomy: A sustainable development strategy - Chavarria, Hugo; Trigo, Eduardo; Villarreal, Federico; Elverdin, Pablo; Piñeiro, Valeria (T20, 2020)
Developing the bioeconomy offers a significant opportunity for achieving the Sustainable Development Goals (SDG) at the global level, while at the same time serve as strategic instruments for addressing new challenges emerging from the COVID-19 global crisis. Advances in science and technology and existing experiences, fully support expectations in this sense. However, effective progress will be only possible if national strategies evolve within a coherent and harmonized global framework. The G20 has a strategic role in promoting this transition not only among its members, but within the broader development community. Three specific lines of action are proposed in support of this transition: (i) a broader agreement on guiding principles for global bioeconomy policymaking; (ii) a framework of credible bioeconomy indicators; and (iii) an effective bioeconomy knowledge management platform.